Acyltransferase skinny hedgehog regulates TGFβ-dependent fibroblast activation in SSc - Liang, Ruifang; Kagwiria, Rosebeth; Zehender, Ariella; Dees, Clara; Bergmann, Christina; Krasowska, Dorota; Michalska-Jakubus, Małgorzata; Kreuter, Alexander; Kraner, Max; Schett, Georg; Distler, Jörg; Ramming, Andreas (Annals of the Rheumatic Diseases, 2019)
Objectives: Systemic sclerosis (SSc) is characterised by aberrant hedgehog signalling in fibrotic tissues. The hedgehog acyltransferase (HHAT) skinny hedgehog catalyses the attachment of palmitate onto sonic hedgehog (SHH). Palmitoylation of SHH is required for multimerisation of SHH proteins, which is thought to promote long-range, endocrine hedgehog signalling. The aim of this study was to evaluate the role of HHAT in the pathogenesis of SSc. Methods: Expression of HHAT was analysed by real-time polymerase chain reaction(RT-PCR), immunofluorescence and histomorphometry. The effects of HHAT knockdown were analysed by reporter assays, target gene studies and quantification of collagen release and myofibroblast differentiation in cultured human fibroblasts and in two mouse models. Results: The expression of HHAT was upregulated in dermal fibroblasts of patients with SSc in a transforming growth factor-β (TGFβ)/SMAD-dependent manner. Knockdown of HHAT reduced TGFβ-induced hedgehog signalling as well as myofibroblast differentiation and collagen release in human dermal fibroblasts. Knockdown of HHAT in the skin of mice ameliorated bleomycin-induced and topoisomerase-induced skin fibrosis. Conclusion: HHAT is regulated in SSc in a TGFβ-dependent manner and in turn stimulates TGFβ-induced long-range hedgehog signalling to promote fibroblast activation and tissue fibrosis. Targeting of HHAT might be a novel approach to more selectively interfere with the profibrotic effects of long-range hedgehog signalling.
CRIS-Team Scopus Importer:2019-06-21
Keywords: dermal fibrosis; hedgehog signaling; skinny hedgehog; systemic sclerosis; TGFβ

A Remorin from Nicotiana benthamiana Interacts with the Pseudomonas Type-III Effector Protein HopZ1a and is Phosphorylated by the Immune-Related Kinase PBS1 - Albers, Philip; Üstün, Suayib; Witzel, Katja; Kraner, Max; Börnke, Frederik (Molecular Plant-Microbe Interactions, 2019)
The plasma membrane (PM) is at the interface of plant–pathogen interactions and, thus, many bacterial type-III effector (T3E) proteins target membrane-associated processes to interfere with immunity. The Pseudomonas syringae T3E HopZ1a is a host cell PM-localized effector protein that has several immunity-associated host targets but also activates effector-triggered immunity in resistant backgrounds. Although HopZ1a has been shown to interfere with early defense signaling at the PM, no dedicated PM-associated HopZ1a target protein has been identified until now. Here, we show that HopZ1a interacts with the PM-associated remorin protein NbREM4 from Nicotiana benthamiana in several independent assays. NbREM4 relocalizes to membrane nanodomains after treatment with the bacterial elicitor flg22 and transient overexpression of NbREM4 in N. benthamiana induces the expression of a subset of defense-related genes. We can further show that NbREM4 interacts with the immune-related receptor-like cytoplasmic kinase avrPphB-susceptible 1 (PBS1) and is phosphorylated by PBS1 on several residues in vitro. Thus, we conclude that NbREM4 is associated with early defense signaling at the PM. The possible relevance of the HopZ1a–NbREM4 interaction for HopZ1a virulence and avirulence functions is discussed.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Bacterial pathogenesis; Defense signaling pathways; Effectors; Elicitors; HopZ1a; MAMPs; PAMPs; PBS1; Pseudomonas syringae; Remorin; Type-3 secretion

Autophagic degradation of lamins facilitates the nuclear egress of herpes simplex virus type 1 - Turan, Aykut; Grosche, Linda; Krawczyk, Adalbert; Mühl-Zürbes, Petra; Drassner, Christina; Düthorn, Alexandra; Kummer, Mirko; Hasenberg, Mike; Voortmann, Sylvia; Jastrow, Holger; Dörrie, Jan; Schaft, Niels; et al. (The Journal of Cell Biology, 2019)
Dendritic cells (DCs) are crucial for the induction of potent antiviral immune responses. In contrast to immature DCs (iDCs), mature DCs (mDCs) are not permissive for infection with herpes simplex virus type 1 (HSV-1). Here, we demonstrate that HSV-1 infection of iDCs and mDCs induces autophagy, which promotes the degradation of lamin A/C, B1, and B2 in iDCs only. This in turn facilitates the nuclear egress of progeny viral capsids and thus the formation of new infectious particles. In contrast, lamin protein levels remain stable in HSV-1-infected mDCs due to an inefficient autophagic flux. Elevated protein levels of KIF1B and KIF2A in mDCs inhibited lamin degradation, likely by hampering autophagosome-lysosome fusion. Therefore, in mDCs, fewer progeny capsids were released from the nuclei into the cytosol, and fewer infectious virions were assembled. We hypothesize that inhibition of autophagic lamin degradation in mDCs represents a very powerful cellular counterstrike to inhibit the production of progeny virus and thus viral spread.
CRIS-Team WoS Importer:2019-02-21

Autophagy-Mediated Breakdown of the nuclear lamina facilitates nuclear egress of HSV-1 capsids and thus generation of progeny virus in dendritic cells - Turan, A.; Krawczyk, A.; Grosche, Linda; Mühl-Zürbes, Petra; Drassner, C.; Hasenberg, M.; Voortmann, S.; Jastrow, H.; Kraner, Max; Doehner, K.; Sodeik, B.; Heilingloh, Christiane; et al. (2018)
EVALuna2:36213

Beyond diphtheria toxin: cytotoxic proteins of Corynebacterium ulcerans and Corynebacterium diphtheriae - Weerasekera, Dulanthi; Möller, Jens; Kraner, Max; Azevedo Antunes de Oliveira, Camila; Mattos-Guaraldi, Ana Luiza; Burkovski, Andreas (Microbiology, 2019)
Diphtheria toxin is one of the best investigated bacterial toxins and the major virulence factor of toxigenic Corynebacterium diphtheriae and Corynebacterium ulcerans strains. However, also diphtheria toxin-free strains of these two species can cause severe infections in animals and humans, indicating the presence of additional virulence factors. In this study, we present a first characterization of two proteins with cytotoxic effect in corynebacteria. A putative ribosome-binding protein (AEG80717, CULC809_00177), first annotated in a genome sequencing project of C. ulcerans strain 809, was investigated in detail together with a homologous protein identified in C. diphtheriae strain HC04 (AEX80148, CDHC04_0155) in this study. The corresponding proteins show striking structural similarity to Shiga-like toxins. Interaction of wild-type, mutant and complementation as well as overexpression strains with invertebrate model systems and cell lines were investigated. Depending on the presence of the corresponding genes, detrimental effects were observed in vivo in two invertebrate model systems, Caenorhabditis elegans and Galleria mellonella, and on various animal and human epithelial and macrophage cell lines in vitro. Taken together, our results support the idea that pathogenicity of corynebacteria is a multifactorial process and that new virulence factors may influence the outcome of potentially fatal corynebacterial infections.
CRIS-Team WoS Importer:2019-08-13

Choline transporter-like1 (CHER1) is crucial for plasmodesmata maturation in Arabidopsis thaliana - Kraner, Max; Link, Katrin; Melzer, Michael; Ekici, Arif Bülent; Uebe, Steffen; Tarazona, Pablo; Feussner, Ivo; Hofmann, Jörg; Sonnewald, Uwe (Plant Journal, 2016)
Plasmodesmata (PD) are microscopic pores connecting plant cells and enable cell-to-cell transport. Currently, little is known about the molecular mechanisms regulating PD formation and development. To uncover components of PD development we made use of the 17 kDa movement protein (MP17) encoded by the Potato leafroll virus (PLRV). The protein is required for cell-to-cell movement of the virus and localises to complex PD. Forward genetic screening for Arabidopsis mutants with altered PD-binding of MP17 revealed several mutant lines, while molecular genetics, biochemical and microscopic studies allowed further characterisation. Map-based cloning of one mutant revealed a point mutation in the choline transporter-like 1 (CHER1) protein, changing glycine(247) into glutamate. Mutation in CHER1 resulted in a starch excess phenotype and stunted growth. Ultrastructure analysis of shoot apical meristems, developing and fully developed leaves showed reduced PD numbers and the absence of complex PD in fully developed leaves. This indicates that cher1 mutants are impaired in PD formation and development. Global lipid profiling revealed only slight modifications in the overall lipid composition, however, altered composition of PD-associated lipids cannot be ruled out. Thus, cher1 is devoid of complex PD in developed leaves and provides insights into the formation of complex PD at the molecular level. This article is protected by copyright. All rights reserved.
EVALuna2:9344

Comparative proteomic profiling of the choline transporter-like1 (CHER1) mutant provides insights into plasmodesmata composition of fully developed Arabidopsis thaliana leaves - Kraner, Max; Müller, Carmen; Sonnewald, Uwe (Plant Journal, 2017)
In plants, intercellular communication and exchange are highly dependent on cell wall bridging structures between adhering cells, so-called plasmodesmata (PD). In our previous genetic screen for PD-deficient Arabidopsis mutants, we described choline transporter-like 1 (CHER1) being important for PD genesis and maturation. Leaves of cher1 mutant plants have up to 10 times less PD, which do not develop to complex structures. Here we utilize the T-DNA insertion mutant cher1-4 and report a deep comparative proteomic workflow for the identification of cell-wall-embedded PD-associated proteins. Analyzing triplicates of cell-wall-enriched fractions in depth by fractionation and quantitative high-resolution mass spectrometry, we compared >5000 proteins obtained from fully developed leaves. Comparative data analysis and subsequent filtering generated a list of 61 proteins being significantly more abundant in Col-0. This list was enriched for previously described PD-associated proteins. To validate PD association of so far uncharacterized proteins, subcellular localization analyses were carried out by confocal laser-scanning microscopy. This study confirmed the association of PD for three out of four selected candidates, indicating that the comparative approach indeed allowed identification of so far undescribed PD-associated proteins. Performing comparative cell wall proteomics of Nicotiana benthamiana tissue, we observed an increase in abundance of these three selected candidates during sink to source transition. Taken together, our comparative proteomic approach revealed a valuable data set of potential PD-associated proteins, which can be used as a resource to unravel the molecular composition of complex PD and to investigate their function in cell-to-cell communication.Significance Statement Plants as multi cellular organisms are composed of various specialised cell types, while most of these cell types are symplasmically connected via plasmodesmata (PD) allowing exchange of nutrients and signal molecules. To date, the molecular composition of PD is not well understood, therefore a comprehensive and comparative proteomic approach was followed to identify proteins providing new insights into the composition of these important communication structures.
Keywords: Arabidopsis thaliana; At3g15380; CHER1; choline transporter-like 1; proteomics; plasmodesmata; endoplasmic reticulum-body; MEE9; At1G22610; At1G51570

Comparative proteomic profiling of the Choline transporter-like1 (CHER1) mutant provides insights into plasmodesmata composition of fully developed Arabidopsis thaliana leaves. - Kraner, Max; Müller, Carmen; Sonnewald, Uwe (Plant Journal, 2017)
In plants, intercellular communication and exchange are highly dependent on cell wall bridging structures between adhering cells, so-called Plasmodesmata (PD). In our previous genetic screen for PD deficient Arabidopsis mutants, we described choline transporter-like 1 (CHER1) being important for PD genesis and maturation. Leaves of cher1 mutant plants have up to 10-times less PD which do not develop to complex structures. Here we utilize the T-DNA insertion mutant cher1-4 and report a deep comparative proteomic workflow for the identification of cell wall embedded PD-associated proteins. Analyzing triplicates of cell wall enriched fractions in depth by fractionation and quantitative high-resolution mass spectrometry, we compared >5000 proteins obtained from fully developed leaves. Comparative data analysis and subsequent filtering generated a list of 61 proteins being significantly more abundant in Col-0. This list was enriched for previously described PD-associated proteins. To validate PD-association of so far uncharacterised proteins, sub-cellular localisation analysis were carried out by confocal laser scanning microscopy (CLSM). This study confirmed PD-association for three out of four selected candidates indicating that the comparative approach indeed allowed identification of so far undescribed PD-associated proteins. Performing comparative cell wall proteomics of Nicotiana benthamiana tissue we observed an increase in abundance of these three selected candidates during sink to source transition. Taken together, our comparative proteomic approach revealed a valuable data set of potential PD-associated proteins, which can be used as resource to unravel the molecular composition of complex PD and to investigate their function in cell-to-cell communication. This article is protected by copyright. All rights reserved.

Hop/Sti1-A Two-Faced Cochaperone Involved in Pattern Recognition Receptor Maturation and Viral Infection - Lamm, Christian; Kraner, Max; Hofmann, Jörg; Boernke, Frederik; Mock, Hans-Peter; Sonnewald, Uwe (Frontiers in Plant Science, 2017)
Perception of pathogens by host pattern recognition receptors (PRRs) or R proteins is a prerequisite to promote successful immune responses. The Hsp70/Hsp90 organizing protein Hop/Sti1, a multifunctional cochaperone, has been implicated in the maturation of a receptor-like kinase (RLK) necessary for chitin sensing. However, it remains unknown whether Hop/Sti1 is generally participating in PRR genesis. Using RNA-interference (RNAi), we silenced Hop/Sti1 expression in Nicotiana tabacum to gain further insight into the role of the cochaperone in plant defense responses. As expected, transgenic plants do not respond to chitin treatment anymore. In contrast to this, trafficking and functionality of the flagellin PRR FLS2 were unaltered, suggesting a selective involvement of Hop/Sti1 during PRR maturation. Furthermore, Hop/Sti1 was identified as a cellular determinant of Potato virus Y (PVY) symptom development in tobacco, since PVY was able to accumulate to near wild-type level without provoking the usual veinal necrosis phenotype. In addition, typical antiviral host defense responses were suppressed in the transgenic plants. These data suggest that perception of PVY is dependent on Hop/Sti1-mediated receptor maturation, while viral symptoms represent a failing attempt to restrict PVY spread. In addition, Hop/Sti1 colocalized with virus-induced membrane aggregates in wild-type plants. The retention of Hop/Sti1 in potential viral replication complexes suggests a role during viral translation/replication, explaining why RNAi-lines do not exhibit increased susceptibility to PVY. This study provides evidence for a dual role of Hop/Sti1 in PRR maturation and pathogen perception as well as in promoting viral proliferation.
Keywords: Hop/Sti1 cochaperone; pattern recognition receptor; CERK1; FLS2; pathogen perception; Nicotiana tabacum cv. Samsun NN; Potato virus Y

Hop/Sti1 - A Two-Faced Cochaperone Involved in Pattern Recognition Receptor Maturation and Viral Infection. - Lamm, Christian; Kraner, Max; Hofmann, Jörg; Boernke, Frederik; Mock, Hans-Peter; Sonnewald, Uwe (Frontiers in Plant Science, 2017)
Perception of pathogens by host pattern recognition receptors (PRRs) or R proteins is a prerequisite to promote successful immune responses. The Hsp70/Hsp90 organizing protein Hop/Sti1, a multifunctional cochaperone, has been implicated in the maturation of a receptor-like kinase (RLK) necessary for chitin sensing. However, it remains unknown whether Hop/Sti1 is generally participating in PRR genesis. Using RNA-interference (RNAi), we silenced Hop/Sti1 expression in Nicotiana tabacum to gain further insight into the role of the cochaperone in plant defense responses. As expected, transgenic plants do not respond to chitin treatment anymore. In contrast to this, trafficking and functionality of the flagellin PRR FLS2 were unaltered, suggesting a selective involvement of Hop/Sti1 during PRR maturation. Furthermore, Hop/Sti1 was identified as a cellular determinant of Potato virus Y (PVY) symptom development in tobacco, since PVY was able to accumulate to near wild-type level without provoking the usual veinal necrosis phenotype. In addition, typical antiviral host defense responses were suppressed in the transgenic plants. These data suggest that perception of PVY is dependent on Hop/Sti1-mediated receptor maturation, while viral symptoms represent a failing attempt to restrict PVY spread. In addition, Hop/Sti1 colocalized with virus-induced membrane aggregates in wild-type plants. The retention of Hop/Sti1 in potential viral replication complexes suggests a role during viral translation/replication, explaining why RNAi-lines do not exhibit increased susceptibility to PVY. This study provides evidence for a dual role of Hop/Sti1 in PRR maturation and pathogen perception as well as in promoting viral proliferation.

Mass Spectrometric Characterization of HSV-1 L-Particles From Human Dendritic Cells and BHK21 Cells and Analysis of Their Functional Role - Birzer, Alexandra; Kraner, Max; Heilingloh, Christiane Silke; Mühl-Zürbes, Petra; Hofmann, Jörg; Steinkasserer, Alexander; Popella, Linda (Frontiers in Microbiology, 2020)
Herpes simplex virus type 1 (HSV-1) is a very common human pathogenic virus among the world’s population. The lytic replication cycle of HSV-1 is, amongst others, characterized by a tripartite viral gene expression cascade, the assembly of nucleocapsids involving their subsequent nuclear egress, tegumentation, re-envelopment and the final release of progeny viral particles. During productive infection of a multitude of different cell types, HSV-1 generates not only infectious heavy (H-) particles, but also non-infectious light (L-) particles, lacking the capsid. In monocyte-derived mature dendritic cells (mDCs), HSV-1 causes a non-productive infection with the predominant release of L-particles. Until now, the generation and function of L-particles is not well understood, however, they are described as factors transferring viral components to the cellular microenvironment. To obtain deeper insights into the L-particle composition, we performed a mass-spectrometry-based analysis of L-particles derived from HSV-1-infected mDCs or BHK21 cells and H-particles from the latter one. In total, we detected 63 viral proteins in both H- and L-particle preparations derived from HSV-1-infected BHK21 cells. In L-particles from HSV-1-infected mDCs we identified 41 viral proteins which are differentially distributed compared to L-particles from BHK21 cells. In this study, we present data suggesting that L-particles modify mDCs and suppress their T cell stimulatory capacity. Due to the plethora of specific viral proteins incorporated into and transmitted by L-particles, it is tempting to speculate that L-particles manipulate non-infected bystander cells for the benefit of the virus.
CRIS-Team Scopus Importer:2020-10-23
Keywords: BHK21 cells; dendritic cells; heavy particles; HSV-1; immunomodulatory effect; light particles; mass spectrometry; T cell stimulation

More than a toxin: Protein inventory of Clostridium tetani toxoid vaccines - Möller, Jens; Kraner, Max; Burkovski, Andreas (Proteomes, 2019)
Clostridium tetani is the etiological agent of tetanus, a life-threatening bacterial infection. The most efficient protection strategy against tetanus is a vaccination with the C. tetani neurotoxin, which is inactivated by formaldehyde-crosslinking. Since we assumed that besides the tetanus toxin, other proteins of C. tetani may also be present in toxoid preparations, we analyzed commercially available vaccines from different countries in respect to their protein content using mass spectrometry. In total 991 proteins could be identified in all five analyzed vaccines, 206 proteins were common in all analyzed vaccines and 54 proteins from the 206 proteins were potential antigens. The additionally present proteins may contribute at least partially to protection against C. tetani infection by supporting the function of the vaccine against the devastating effects of the tetanus toxin indirectly. Two different label-free protein quantification methods were applied for an estimation of protein contents. Similar results were obtained with a Total Protein Approach (TPA)-based method and Protein Discoverer 2.2 software package based on the minora algorithm. Depending on the tetanus toxoid vaccine and the quantification method used, tetanus neurotoxin contributes between 14 and 76 % to the total C. tetani protein content and varying numbers of other C. tetani proteins were detected.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Clostridium tetani; Label-free quantification; Neurotoxin; Proteomics; Tetanospasmin; Vaccination

Multiple C2 domains and transmembrane region proteins (MCTPs) tether membranes at plasmodesmata - Brault, Marie L.; Petit, Jules D.; Immel, Françoise; Nicolas, William J.; Glavier, Marie; Brocard, Lysiane; Gaston, Amèlia; Fouché, Mathieu; Hawkins, Timothy J.; Crowet, Jean Marc; Grison, Magali S.; Germain, Véronique; et al. (EMBO Reports, 2019)
In eukaryotes, membrane contact sites (MCS) allow direct communication between organelles. Plants have evolved a unique type of MCS, inside intercellular pores, the plasmodesmata, where endoplasmic reticulum (ER)–plasma membrane (PM) contacts coincide with regulation of cell-to-cell signalling. The molecular mechanism and function of membrane tethering within plasmodesmata remain unknown. Here, we show that the multiple C2 domains and transmembrane region protein (MCTP) family, key regulators of cell-to-cell signalling in plants, act as ER-PM tethers specifically at plasmodesmata. We report that MCTPs are plasmodesmata proteins that insert into the ER via their transmembrane region while their C2 domains dock to the PM through interaction with anionic phospholipids. A Atmctp3/Atmctp4 loss of function mutant induces plant developmental defects, impaired plasmodesmata function and composition, while MCTP4 expression in a yeast Δtether mutant partially restores ER-PM tethering. Our data suggest that MCTPs are unique membrane tethers controlling both ER-PM contacts and cell-to-cell signalling.
CRIS-Team Scopus Importer:2019-07-19
Keywords: ER-PM membrane contact sites; intercellular communication in plants; multiple C2 domains and transmembrane region proteins; plasmodesmata

Probing the potential of CnaB-type domains for the design of tag/catcher systems - Pröschel, Marlene; Kraner, Max; Horn, Anselm; Schäfer, Lena; Sonnewald, Uwe; Sticht, Heinrich (PLoS ONE, 2017)
Building proteins into larger, post-translational assemblies in a defined and stable way is still a challenging task. A promising approach relies on so-called tag/catcher systems that are fused to the proteins of interest and allow a durable linkage via covalent intermolecular bonds. Tags and catchers are generated by splitting protein domains that contain intramolecular isopeptide or ester bonds that form autocatalytically under physiological conditions. There are already numerous biotechnological and medical applications that demonstrate the usefulness of covalent linkages mediated by these systems. Additional covalent tag/catcher systems would allow creating more complex and ultra-stable protein architectures and networks. Two of the presently available tag/catcher systems were derived from closely related CnaB-domains of Streptococcus pyogenes and Streptococcus dysgalactiae proteins. However, it is unclear whether domain splitting is generally tolerated within the CnaBfamily or only by a small subset of these domains. To address this point, we have selected a set of four CnaB domains of low sequence similarity and characterized the resulting tag/catcher systems by computational and experimental methods. Experimental testing for intermolecular isopeptide bond formation demonstrated two of the four systems to be functional. For these two systems length and sequence variations of the peptide tags were investigated revealing only a relatively small effect on the efficiency of the reaction. Our study suggests that splitting into tag and catcher moieties is tolerated by a significant portion of the naturally occurring CnaB-domains, thus providing a large reservoir for the design of novel tag/catcher system

Proteomics of Bordetella pertussis whole-cell and acellular vaccines - Möller, Jens; Kraner, Max; Burkovski, Andreas (BMC Research Notes, 2019)
Objectives: Bordetella pertussis is the etiological agent of whooping cough, a bacterial infection of especially children, which may be fatal without treatment. In frame of studies to investigate putative effects of vaccination on host-pathogen interaction and clonal distribution of strains, in addition to Corynebacterium diphtheriae and Clostridium tetani toxoid vaccines, also whole-cell and acellular pertussis vaccines were analyzed by mass spectrometry. Data description: LC-MS/MS spectra were generated and analyzed using B. pertussis genome data and proteins present in whole-cell and acellular pertussis vaccines were identified. Subcellular localization of proteins and presence of signal peptides was determined bioinformatically.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Bordetella; DTP vaccine; LC-MS/MS; Mass spectrometry; Pertussis; Vaccination; Whooping cough

Proteomics of diphtheria toxoid vaccines reveals multiple proteins that are immunogenic and may contribute to protection of humans against Corynebacterium diphtheriae - Möller, Jens; Kraner, Max; Sonnewald, Uwe; Sangal, Vartul; Tittlbach, Hannes; Winkler, Julia; Winkler, Thomas; Melnikov, Vyacheslav; Lang, Roland; Sing, Andreas; Mattos-Guaraldi, Ana Luiza; Burkovski, Andreas (Vaccine, 2019)
Introduced for mass immunization in the 1920s, vaccines against diphtheria are among the oldest and safest vaccines known. The basic principle of their production is the inactivation of purified diphtheria toxin by formaldehyde cross-linking, which converts the potentially fatal toxin in a completely harmless protein aggregate, which is still immunogenic. Since in addition to diphtheria toxin also other proteins may be secreted by Corynebacterium diphtheriae during cultivation, we assumed that diphtheria toxoid might not be the only component present in the vaccine. To address this question, we established a protocol to reverse formaldehyde cross-linking and carried out mass spectrometric analyses. Different secreted, membrane-associated and cytoplasmic proteins of C. diphtheriae were detected in several vaccine preparations from across the world. Based on these results, bioinformatics and Western blot analyses were applied to characterize if these proteins are immunogenic and may therefore support protection against C. diphtheriae. In frame of this study, we could show that the C. diphtheriae toxoid vaccines induce antibodies against different C. diphtheriae proteins and against diphtheria toxin secreted by Corynebacterium ulcerans, an emerging pathogen which is outnumbering C. diphtheriae as cause of diphtheria-like illness in Western Europe.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Corynebacteria; Corynebacterium ulcerans; Exoproteome; Mass spectrometry; Proteomics; Secretome; Vaccination

Proteomics of isolated sieve tubes from Nicotiana tabacum: sieve element–specific proteins reveal differentiation of the endomembrane system - Liu, Yan; Vasina, Viktoriya V.; Kraner, Max; Peters, Winfried S.; Sonnewald, Uwe; Knoblauch, Michael (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Symplasmicly connected cells called sieve elements form a network of tubes in the phloem of vascular plants. Sieve elements have essential functions as they provide routes for photoassimilate distribution, the exchange of developmental signals, and the coordination of defense responses. Nonetheless, they are the least understood main type of plant cells. They are extremely sensitive, possess a reduced endomembrane system without Golgi apparatus, and lack nuclei and translation machineries, so that transcriptomics and similar techniques cannot be applied. Moreover, the analysis of phloem exudates as a proxy for sieve element composition is marred by methodological problems. We developed a simple protocol for the isolation of sieve elements from leaves and stems of Nicotiana tabacum at sufficient amounts for large-scale proteome analysis. By quantifying the enrichment of individual proteins in purified sieve element relative to bulk phloem preparations, proteins of increased likelyhood to function specifically in sieve elements were identified. To evaluate the validity of this approach, yellow fluorescent protein constructs of genes encoding three of the candidate proteins were expressed in plants. Tagged proteins occurred exclusively in sieve elements. Two of them, a putative cytochrome b561/ferric reductase and a reticulon-like protein, appeared restricted to segments of the endoplasmic reticulum (ER) that were inaccessible to green fluorescent protein dissolved in the ER lumen, suggesting a previously unknown differentiation of the endomembrane system in sieve elements. Evidently, our list of promising candidate proteins (SI Appendix, Table S1) provides a valuable exploratory tool for sieve element biology.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Phloem; Proteomics; Sieve element; Sieve tube endomembrane system

Symplasmic phloem unloading and radial post-phloem transport via vascular rays in tuberous roots of Manihot esculenta - Mehdi, Rabih; Lamm, Christian; Bodampalli Anjanappa, Ravi; Müdsam, Christina; Saeed, Muhammad; Klima, Janine; Kraner, Max; Ludewig, Frank; Knoblauch, Michael; Gruissem, Wilhelm; Sonnewald, Uwe; Zierer, Wolfgang (Journal of Experimental Botany, 2019)
Cassava (Manihot esculenta) is one of the most important staple food crops worldwide. Its starchy tuberous roots supply over 800 million people with carbohydrates. Yet, surprisingly little is known about the processes involved in filling of those vital storage organs. A better understanding of cassava carbohydrate allocation and starch storage is key to improving storage root yield. Here, we studied cassava morphology and phloem sap flow from source to sink using transgenic pAtSUC2::GFP plants, the phloem tracers esculin and 5(6)-carboxyfluorescein diacetate, as well as several staining techniques. We show that cassava performs apoplasmic phloem loading in source leaves and symplasmic unloading into phloem parenchyma cells of tuberous roots. We demonstrate that vascular rays play an important role in radial transport from the phloem to xylem parenchyma cells in tuberous roots. Furthermore, enzymatic and proteomic measurements of storage root tissues confirmed high abundance and activity of enzymes involved in the sucrose synthase-mediated pathway and indicated that starch is stored most efficiently in the outer xylem layers of tuberous roots. Our findings form the basis for biotechnological approaches aimed at improved phloem loading and enhanced carbohydrate allocation and storage in order to increase tuberous root yield of cassava.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Apoplast; cassava; CFDA; esculin; morphology; phloem; ray; starch; SUC2; symplast